Knowledge, attitudes, and practices of healthcare professionals regarding rabies in tertiary care hospitals: A cross-sectional study in Peshawar, Pakistan. - Adnan Ahmad; Fawad Inayat; Noor Ullah; Shaista Rasul; Shehnaz Bakhtiar; Zar Shad; Zakir Ahmad (Public Library of Science (PLoS), 2024)
Background Rabies, caused by the rhabdovirus, is a fatal zoonotic disease with over 59,000 annual deaths globally. Asia and Africa account for 95%, with India leading, followed by China. In Pakistan, where it's endemic, over 50,000 cases are reported yearly. Controlling rabid dog populations through vaccination is crucial in curbing mortality. This research aimed to evaluate healthcare professionals' knowledge, attitudes, and practices concerning rabies in Peshawar, Pakistan. Methods The study was conducted at different tertiary care hospitals in Peshawar, Pakistan from 16 August 2021 to 15 February 2022. Cross-sectional research was conducted to gather data from a total of 100 healthcare workers representing different sections within the healthcare field, including Medical Officers, House Officers, Faculty Staff, Nurses, and Paramedics. Data on knowledge, attitudes, and practices about rabies were collected using a standardized questionnaire. The data analysis included using descriptive statistics and chi-square testing to ascertain potential correlations. Results Among the healthcare professionals, 68 (68%) were males, and 32 (32%) were females. Profession-wise, the included professionals were Nurses 31 (31%), Medical Officers 27 (27%), House officers 26 (26%), paramedical staff 13 (13%), and faculty staff 3 (3%). 91 (91%) and 9 (9%) healthcare professionals responded that dogs and cats are responsible for rabies transmission, respectively. Moreover, 82 (82%) individuals responded that animal bite plays a vital role in the transmission of rabies, whilst 76 (76%) individuals responded that rabies transferred from human to human. 82 (82%) individuals replied that the anti-rabies vaccine (ARV) is the treatment of choice for rabies. Furthermore, 78 (78%) individuals responded that ARV is safe in pregnancy and lactation. Moreover, after being asked about the perception of the health care professionals about the failure in controlling rabies, their responses were unavailability of ARV/RIG 41 (41%), lack of control of stray dogs 34 (34%), lack of awareness 20 (20%). The study revealed statistically significant correlations between healthcare occupations and variables: knowledge of animals responsible for transmitting rabies (p = 0.024) and awareness of human-to-human transmission (p = 0.007). Significant disparities were noted in understanding rabies transmission through contaminated water (p = 0.002). There were variations in attitudes and practices seen across different positions, particularly about views about home treatments (p = 0.033) and the perceived effectiveness of cleansing bite wounds (p = 0.010). Disparities in perceptions of rabies treatment and the accessibility of anti-rabies vaccines and immunoglobulin were observed, with variations based on individual roles. Conclusion The present research elucidates variations in rabies knowledge, attitudes, and practices among healthcare workers, specifically concerning their respective roles. Tailored training programs and standardized practices play a crucial role in mitigating these discrepancies, fostering a greater understanding of rabies, and enhancing the quality of patient treatment. It is recommended that future studies undertake an assessment of the efficacy of therapies and advocate for the adoption of collaborative One Health strategies in the realm of rabies management.